(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the pedagogical foundations of the development of military-patriotic qualities in young people, military culture and its specific features in ensuring the protection of the Motherland, its national security, territorial integrity and sovereignty. The place and role of military culture competences in the formation of military culture skills and qualifications in young people were studied, and the social and pedagogical issues of military culture were considered.